Mainstreaming of LED technologies gets investment boost in Thailand - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The NAMA facility funded with 250k Euro the development of a Thai Rice NAMA full proposal that highlights LED measures for low-emission rice farming. The proposal expects to reach 100,000 rice farmers and 420 agricultural mitigation service providers in 6 provinces of Thailand potentially contributing to GHG reduction of about 1 million tons of CO2eq and transforming the rice sector in target provinces towards low-carbon production.